Case Series: Development of Polyps as a Late Effect After Total Body Irradiation-based Hematopoietic Cell Transplantation in Children With High-risk Leukemia. Issue 8 (November 2021) - Knight, Benjamin; Anderson, Lynnette; Lerner, Diana; Phelan, Rachel; Thakar, Monica S.
Abstract : Advancements in hematopoietic cell transplantation (HCT) have led to increased survivorship rates in many childhood diseases. However, this growing group of long-term survivors face a myriad of late effects. There are currently limited guidelines for surveillance of gastrointestinal polyps for pediatric transplant patients. Here we describe 5 patients undergoing HCT with total body irradiation-based conditioning regimens for leukemia who developed symptomatic polyps a median of 4.5 (range: 0.75 to 5.75) years after HCT. Because of limited surveillance guidelines in children, we conclude that the development of new or progressive symptoms related to the gastrointestinal tract deserves prompt recognition and evaluation.